Faktore by die aankoop van 'n motor vir privaatgebruik - P. J. Du Plessis; P. L.S. Ackermann (South African Journal of Business Management, 1987)
– In this study an attempt is made to establish underlying dimensions from the various evaluation criteria a consumer considers when buying a motor vehicle. The sample consists of 902 consumers of all race groups in mainly metropolitan areas in South Africa who bought a new or used car for private use during the period December 1985 - May 1986. With the aid of principal-factor analysis 12 underlying dimensions out of 65 evaluation criteria were identified, namely: dealer orientation, maintenance, space convenience, driving comfort, mechanical performance, appearance, social influence, manufacturing, choice reinforcement, technical priority, discount and reputation. These factors may serve as a guideline for marketing managers to develop strategies regarding benefit segmentation, promotion and positioning.
Keywords: 650